2020
DOI: 10.1063/5.0009477
|View full text |Cite
|
Sign up to set email alerts
|

The role of faceting in biaxially textured thin films: Columnar morphology and abnormal tilting

Abstract: The groundbreaking properties of biaxially textured thin films have attracted increasing attention to the characterization and growth theory of their crystal morphologies. In particular, multi-faceted columnar structures developed during oblique angle deposition (OAD) show abnormal tilt angles that have not been previously captured by existing models. Current theories for the formation of biaxially aligned columnar structures overlook the fact that the surface diffusion on individual facets can be finite. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…With this respect, we notice that simulations including a more detailed description of flux distributions, e.g. shadowing effects 23,69 , may change the material supply within the same facets, thus slightly altering the material redistribution dynamics predicted by the present set of parameters. The implementation of flux shadowing in the phase-field approach 70 goes beyond the scope of this work as it would require computationally demanding calculations in 3D.…”
Section: Model Calibrationmentioning
confidence: 91%
“…With this respect, we notice that simulations including a more detailed description of flux distributions, e.g. shadowing effects 23,69 , may change the material supply within the same facets, thus slightly altering the material redistribution dynamics predicted by the present set of parameters. The implementation of flux shadowing in the phase-field approach 70 goes beyond the scope of this work as it would require computationally demanding calculations in 3D.…”
Section: Model Calibrationmentioning
confidence: 91%
“…33 In the previous work, we proposed a phase field model incorporating detailed treatments of both process-specific shadowing growth and faceting driven by anisotropic surface energies to study the morphology of nanorods grown by oblique angle deposition. 34 It was found that the film morphology is influenced not only by the uni-directional flux due to ballistic transport but also by the strength of adparticle mobility in relation to asymmetric surface diffusion. We showed that shadowing and directional sticking coefficients were important for growing films with abnormal columnar tilting observed experimentally in two cubic crystals, MgO and CaF 2 .…”
mentioning
confidence: 99%
“…In our previous work, a continuum model was formulated that describes an interfacial growth problem posed by two competing effects, i.e., the protuberances formed on the solid-gas interface following the ballistic trajectories of ad-particles and the stabilizing capillary forces due to surface diffusion. 34 The solid phase and the gas phase are treated as superimposed continua using the thermodynamically consistent diffuse-interface theory. Particle-size effects are ignored, because very little of the complex chemistry involved in CVD is known.…”
mentioning
confidence: 99%
See 1 more Smart Citation